Ojkonimy świadectwem językowego, kulturowego, historycznego i przyrodniczego dziedzictwa Krajny - Kołatka, Krzysztof (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
There is no doubt that toponyms constitute an unusually valuable source of knowledge about a given territory. Geographical names retain the most essential characteristics which make up their distinctive and unique images. Thus, oiconyms, anoiconyms, hydronyms or oronyms are becoming extremely important elements which build a sense of territorial identity in the inhabitants of any area. The mentioned findings also refer to the toponyms from the Krajna region. Because of many controversies concerning the precise geographical scope of this region located on the borderland between Great Poland and Pomerania, these inquiries assume that its area coincides with the borders of the old, pre-partition Nakło Poviat. The subject of the article is the analysis of the Krajna oiconyms carried out by paying special attention to the linguistic, cultural, historical and natural factors of the region. The characterization of the local names includes first of all an etymological-motivational aspect, giving special consideration to their cultural character. However, the fundamental aim of this study is an attempt to reconstruct the linguistic, cultural, historical and natural image of the Krajna region based on the names of towns, villages, settlements and colonies.